Performance Problem Diagnostics by Systematic Experimentation - Wert, Alexander (The Karlsruhe Series on Software Design and Quality / Ed. by Prof. Dr. Ralf Reussner, 2018)
In this book, we introduce an automatic, experiment-based approach for performance problem diagnostics in enterprise software systems. The proposed approach systematically searches for root causes of detected performance problems by executing series of systematic performance tests. The presented approach is evaluated by various case studies showing that the presented approach is applicable to a wide range of contexts.